2020
DOI: 10.1177/0883073820909274
|View full text |Cite
|
Sign up to set email alerts
|

Brain Stiffness Relates to Dynamic Balance Reactions in Children With Cerebral Palsy

Abstract: Cerebral palsy is a neurodevelopmental movement disorder that affects coordination and balance. Therapeutic treatments for balance deficiencies in this population primarily focus on the musculoskeletal system, whereas the neural basis of balance impairment is often overlooked. Magnetic resonance elastography (MRE) is an emerging technique that has the ability to sensitively assess microstructural brain health through in vivo measurements of neural tissue stiffness. Using magnetic resonance elastography, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
7
1
Order By: Relevance
“…< 35 years or > 65 years), we did not observe any significant correlations between either HCsf or and memory task outcomes in either group, though these subsamples are smaller and less powered to detect such effects, and a future study designed to understand how these structure-function relationships may change across the lifespan is warranted. We note that in recent studies on pediatric participants, MRE structure-function relationships were observed in but not (McIlvain et al, 2020a(McIlvain et al, , 2020b. We also recognize that this study shows weaker evidence of structure-function dissociations than in our prior MRE work that reported a double dissociation in structurefunction relationships of relational memory and fluid intelligence performance with viscoelasticity of the HC and orbitofrontal cortex (Johnson et al, 2018).…”
contrasting
confidence: 57%
“…< 35 years or > 65 years), we did not observe any significant correlations between either HCsf or and memory task outcomes in either group, though these subsamples are smaller and less powered to detect such effects, and a future study designed to understand how these structure-function relationships may change across the lifespan is warranted. We note that in recent studies on pediatric participants, MRE structure-function relationships were observed in but not (McIlvain et al, 2020a(McIlvain et al, , 2020b. We also recognize that this study shows weaker evidence of structure-function dissociations than in our prior MRE work that reported a double dissociation in structurefunction relationships of relational memory and fluid intelligence performance with viscoelasticity of the HC and orbitofrontal cortex (Johnson et al, 2018).…”
contrasting
confidence: 57%
“…Previous reports that include data from some or all of these participants focused on the relationships of age, standing sway, and balance reactions in typical development, 18 gait stability in children with and without spastic CP, 19 magnetic resonance elastography to evaluate brain tissue viscoelasticity of the two groups, 20 and the relationship between balance reaction performance and brain viscoelasticity in children with spastic CP. 21 What this paper adds…”
Section: Other Study Aspectsmentioning
confidence: 92%
“…This report focuses on results from balance‐reaction tests, which represent part of a larger, single‐session protocol more broadly assessing balance, gait, and physical activity. Previous reports that include data from some or all of these participants focused on the relationships of age, standing sway, and balance reactions in typical development, gait stability in children with and without spastic CP, magnetic resonance elastography to evaluate brain tissue viscoelasticity of the two groups, and the relationship between balance reaction performance and brain viscoelasticity in children with spastic CP …”
Section: Methodsmentioning
confidence: 99%
“… 29 , 34 In later studies by the same group, brain stiffness and cognition were shown to relate in paediatric cerebral palsy and adolescent risk-taking tasks. 38 , 39 Furthermore, a detailed assessment of the relation between hippocampal subfield stiffness and specific aspects of memory was reported. 37 However, less is known about the relationship between mechanical properties and cognitive function in older adults and how this relationship is related to specific pathologies that can be measured by other modalities.…”
Section: Introductionmentioning
confidence: 99%